Analisis Kompleksitas Algoritma Filter IRR Shen-Castan untuk Deteksi Tepi pada Citra Digital - Dewi Anggraini Puspa Hapsari; Widya Khafa Nofa; Sugeng Santoso (Universitas Raharja, 2019)
This study aims to measurethe level of complexity of a Shen-Castan IIR filter algorithm for edge detection in digital images based on time complexity and space complexity. This analysis is very helpful when going to do an algorithm optimization and data structure that will be used in a system. Time complexity states how long an algorithm runs at runtime based on the input given. While space complexity states how much space in memory an algorithm needs when operating. The calculation of time complexity and space complexity is denoted by Big-O notation. From the results of time complexity calculations obtained if the Shen-Castan IIR filter algorithm has the complexity of the O (n) algorithm and requires space complexity O (n) where the algorithm will need at least N units of space in memory and depends on the length of the array.